Editorial - In the Kingdom of the Blind, the One-Eyed Man is King: The Case for The International Journal of Statistics in Medical Research - Biondi-Zoccai, Giuseppe (International Journal of Statistics in Medical Research, 2013)
International Journal of Criminology and Sociology, Volume 2 Number 1, Editorial